2023
DOI: 10.1039/d2dt03369k
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water

Abstract: The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any methods. However, the challenges to overcome are many, and critically the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Similarly, research efforts are being devoted for constructing protective layers as an effective strategy for improving the OER stability for seawater electrolysis. Wang et al demonstrated the use of NiMoO x as a protective layer on BiVO 4 for PEC seawater splitting; the photoanode showed a J p of 3.3 mA cm –2 . , Zhou et al used an RhO 2 -modified Mo-BiVO 4 for direct seawater splitting and obtained a stable J p of 2.16 mA cm –2 in natural seawater at 1.0 V RHE . Another group led by Zhou et al reported seawater splitting using TiO@g-C 3 N 4 decorated with Co-Pi, which showed a J p of ∼1.8 mA cm –2 . [32] The role of Co as a cocatalyst for providing the redox reaction site was demonstrated by Gopinath et al, who observed a photocurrent density of 190 μA cm –2 under simulated seawater .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, research efforts are being devoted for constructing protective layers as an effective strategy for improving the OER stability for seawater electrolysis. Wang et al demonstrated the use of NiMoO x as a protective layer on BiVO 4 for PEC seawater splitting; the photoanode showed a J p of 3.3 mA cm –2 . , Zhou et al used an RhO 2 -modified Mo-BiVO 4 for direct seawater splitting and obtained a stable J p of 2.16 mA cm –2 in natural seawater at 1.0 V RHE . Another group led by Zhou et al reported seawater splitting using TiO@g-C 3 N 4 decorated with Co-Pi, which showed a J p of ∼1.8 mA cm –2 . [32] The role of Co as a cocatalyst for providing the redox reaction site was demonstrated by Gopinath et al, who observed a photocurrent density of 190 μA cm –2 under simulated seawater .…”
Section: Introductionmentioning
confidence: 99%
“…Another group led by Zhou et al reported seawater splitting using TiO@g-C 3 N 4 decorated with Co-Pi, which showed a J p of ∼1.8 mA cm –2 . [32] The role of Co as a cocatalyst for providing the redox reaction site was demonstrated by Gopinath et al, who observed a photocurrent density of 190 μA cm –2 under simulated seawater . However, the protective layers may cover the active sites and inhibit the catalytic process. , Thus, it is challenging to simultaneously improve the photocurrent efficiency and stability of the photoelectrocatalysts in direct seawater PEC reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the sustainability considerations, only oxide based systems are considered, such as TiO 2 , BiVO 4 , and WO 3 . 17–22 Among these, TiO 2 and BiVO 4 exhibit comparable bulk conduction band (CB) potentials, which are suitable for CO 2 reduction 23–25 and H 2 generation, 26–28 apart from water oxidation. It is also important to completely avoid or minimize H 2 generation, so that C1-oxygenates can be maximized, by choosing the right co-catalyst; this indicates the redox sites should be well-separated.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noted that photons around 500 ± 50 nm exhibit the highest wattage per unit area (∼1.4–1.6 W m −2 nm −1 ) of illumination, 29 and it is prudent to make use of these photons for chemical conversion. By decreasing the particle size of BiVO 4 , 28 it is possible to fine tune the CB potential along with the photovoltage and photocurrent, which would help to (a) achieve and fine tune the CO 2 reduction to a specific product in a predominant way, and/or (b) transfer the excited electrons into the CB of TiO 2 . Indeed, the idea of suitably combining a wide E g semiconductor and visible light absorbing water oxidation photocatalyst with a staggered type-II heterojunction is worth evaluating, as such a combination would meet the potential requirements of CO 2 reduction.…”
Section: Introductionmentioning
confidence: 99%